Effect of fly ash on freeze–thaw durability of concrete in marine environment. Issue 2 (3rd April 2018) - Islam, Md. M.; Alam, Mohammad Tarequl; Islam, Md. S.
Abstract: Deterioration of structural concrete exposed to freeze–thaw cycles is one of the most important durability problems under subzero temperature conditions. It becomes more devastating when associated with marine environment. Supplementary cementitious material such as fly ash may be used as partial replacement of cement for making more dense, less absorptive and less permeable concrete which improve freeze–thaw durability. This paper presents a part of an experimental study on the freeze–thaw effect of concrete specimens exposed to artificial seawater simulating marine environment and plain water over 360 cycles. Three different grades of concrete M38, M33 and M28, each with four different fly ash replacement level, 20, 30, 40 and 60% were used for the experimental programme. The deteriorative effects were measured by studying weight and volume change, compressive strength, permeability characteristics and rapid chloride penetration resistance of the deteriorated test specimens. the optimum amount of cement replacement is reported to be around 30 to 40%. The study reveals that fly ash concrete has better resistance against freeze–thaw deterioration due to pozzolanic activity of fly ashes that creates more calcium silicate hydrate gel and fills pore spaces, which can effectively reduce the corrosion of the embedded steel reinforcement.